Determination of fault planes and dimensions for low-magnitude earthquakes – A case study in eastern Taiwan. (March 2017) - Mozziconacci, Laetitia; Delouis, Bertrand; Huang, Bor-Shouh
Highlights: Focal mechanism and fault plane determination of small earthquakes. Fault length determination of small earthquakes. 2006 Taitung crisis, eastern Taiwan. Abstract: We present a modified version of the FMNEAR method for determining the focal mechanisms and fault plane geometries of small earthquakes. Our improvements allow determination of the fault plane and dimensions using the near-field components of only a few local records. The limiting factor is the number of stations: a minimum of five to six stations is required to discriminate between the fault plane and auxiliary plane. This limitation corresponds to events with magnitudes ML  > 3.5 in eastern Taiwan, but strongly depends on station coverage in the study area. Once a fault plane is identified, it is provided along with its source time function and fault slip distribution. The proposed approach is validated by synthetic tests, and applied to real cases from a seismic crisis that occurred in the Longitudinal Valley of eastern Taiwan in April 2006. The fault geometries and faulting types of test events closely match the fault system of the main shock and reveal a minor one inside the faults zone of the Longitudinal Valley. Tested on a larger scale, this approach enables the fault geometries of main and secondary fault systems to be recovered from small earthquakes, allowing subsurface faults to be mapped in detail without waiting for a large, damaging event.